Abundance and Distribution of Phlebotomus pedifer (Diptera: Psychodidae) Across Various Habitat Types in Endemic Foci of Cutaneous Leishmaniasis in the Mid-Highlands of Wolaita Zone, Southern Ethiopia - Bereket Alemayehu; Temesgen Tomas; Negese Koroto; Teshome Matusala; Aberham Megaze; Herwig Leirs (Tropical Medicine and Infectious Disease)
Phlebotomus pedifer is a vector of Leishmania aethiopica, the causative agent of cutaneous leishmaniasis. This study assessed the abundance and distribution of P. pedifer in different habitats and human houses situated at varying distances from hyrax (reservoir host) dwellings, in Wolaita Zone, southern Ethiopia. Sandflies were collected from January 2020 to December 2021 using CDC light traps, sticky paper traps, and locally made emergence traps. Sampling was performed in human houses, peri-domestic areas, farmlands, and hyrax dwellings. Houses 200 m and 400 m from hyrax dwellings were selected to study whether distance affects indoor sandfly abundance. A total of 2485 sandflies were captured, with P. pedifer accounting for 86.1% of the catch and Sergentomyia spp. comprising the remaining 13.9%. The abundance of P. pedifer was highest in human houses (72.3%) and lowest in farmlands (4.0%). Temperature showed a positive correlation with sandfly abundance (r = 0.434, p = 0.000), while rainfall (r = −0.424, p = 0.001) and humidity (r = −0.381, p = 0.001) were negatively correlated with abundance. Houses near hyrax dwellings had significantly higher P. pedifer abundance compared to those further away. Soil-emergence trapping yielded only a few P. pedifer specimens, primarily from hyrax dwellings. The findings highlight the increased presence of P. pedifer indoors, particularly in houses close to hyrax habitats, emphasizing the need for targeted indoor vector control strategies to mitigate the risk of cutaneous leishmaniasis transmission.